2004
DOI: 10.1093/jpepsy/jsh022
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder (PTSD) and Posttraumatic Stress Symptoms (PTSS) in Families of Adolescent Childhood Cancer Survivors

Abstract: Both PTSD and PTSS help in understanding the experience of adolescent cancer survivors and their families. Within families of childhood cancer survivors, it is likely that some member may be experiencing treatable bothersome memories, arousal, or avoidance specific to the cancer experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
345
6
14

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(402 citation statements)
references
References 31 publications
32
345
6
14
Order By: Relevance
“…This finding somewhat contradict the conclusions of previous studies reporting gender differences. Typically, those studies have merely compared the scores of mothers with those of fathers, and often found that mothers report more distress than fathers do (e.g., [4,6]), although other times no such gender differences are found (e.g., [10,26]). Relying on the approach used in the present study, we may conclude that the experience of the child's illness often is as stressful for fathers as for mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding somewhat contradict the conclusions of previous studies reporting gender differences. Typically, those studies have merely compared the scores of mothers with those of fathers, and often found that mothers report more distress than fathers do (e.g., [4,6]), although other times no such gender differences are found (e.g., [10,26]). Relying on the approach used in the present study, we may conclude that the experience of the child's illness often is as stressful for fathers as for mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress (PTS) symptoms, including the clinical diagnosis of PTSD, has been suggested to be a useful model for understanding long-term distress in parents of children with cancer [9], and the characteristic symptoms intrusion, avoidance and hyperarousal have been observed in parents of children who survive (e.g. [10]). On the basis of an extensive review, Smith et al [11] note that the estimated rates of PTS and PTSD are often even higher in parents of children with cancer than in pediatric and adult cancer patients themselves.…”
mentioning
confidence: 99%
“…Heightened levels of depression [6,7], anxiety [8][9][10][11], stress [10,12], a decreased quality of life [13], marital distress [14,15] and post-traumatic stress symptoms (e.g. [16][17][18]) have been reported in parents of pediatric cancer patients. This effect has been found to persist in a substantial proportion of the parents, 5 to even 10 years or longer [12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that dealing with childhood cancer is a dramatic event that could influence physical and psychosocial functioning long time after termination of the treatment [2,5,6]. In addition, post-traumatic stress symptoms appeared to be common in families of childhood cancer; among survivors of childhood cancer, as well as among their parents [7][8][9][10]. Nevertheless, many long-term survivors of childhood cancer turned out to function well [11,12](see reviews by Langeveld et al [3] and Stam et al [4]).…”
Section: Introductionmentioning
confidence: 99%